Reconceptualizing Support Services for Classroom Teachers Implications for Teacher Education - Pugach, Marleen; Lilly, M. Stephen ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A critical examination of problems in delivery services to students with mild learning and behavior problems points out weaknesses in special education programs. These programs have grown indiscriminately, resulting in over-identification of "handicapped" students. The special education placement system is time-consuming and is not the most effective alternative if the goal is to support teachers and help students succeed in the regular classroom. Special education diagnostic, labeling, and instructional procedures have always set it apart from regular education, and presumed differences between students, teachers, and curricular approaches in special and regular education have been overstressed. Increasing numbers of educators are recognizing this "myth of differentness" and are starting to build a common ground, free from misleading categorical labels for children and teachers, and focusing on defining the common elements of regular and special education. Accepting diversity as a norm for regular classrooms can lead to development of alternative group structures, intensive tutoring, or alternative pacing, and these services can be provided by support teachers working within the classroom with the regular teacher. A redefinition is needed in schools of education of the appropriate relationship between programs preparing classroom teachers and those preparing support services personnel. (JD)
ERIC Note: Paper presented at the Annual Meeting of the American Association of Colleges for Teacher Education (36th, San Antonio, TX, February 1-4, 1984).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Learning Disabilities; Mainstreaming; Mild Mental Retardation; Remedial Programs; Resource Teachers; Shared Services; Special Education; Teacher Education; Teacher Role; Teamwork; Speeches/Meeting Papers; Reports, Descriptive